The prescription - Castillo Freyre, Mario (2024)
The article examines the scope of prescription as regulated by Article 1989 of the Peruvian Civil Code, which states that “Prescription extinguishes the action, but not the right itself.” Through a detailed analysis, the authors explore the distinctions between action and claim, as well as the relevance of the passage of time in prescription.They also examine the concept of a subsisting but unenforceable right and its treatment within the Peruvian legal system. The main conclusion is that, although prescription affects the enforceability of the pretension, the right of action itself is not extinguished and remains accessible in future judicial proceedings.